2022-RA-837-ESGO Characterization of long-term survivor and maintenance therapy in relapsed ovarian cancer (CAROLIN)- Intergroup study NOGGO/A-AGO. (20th October 2022) - Grabowski, Jacek; Braicu, Ioana Elena; Petru, Edgar; Woopen, Hannah; Müller, Andreas; Virk, Yasemin; Bogner, Gerhard; Hensel, Manfred; Zocholl, Dario; Eggemann, Holm; Marth, Christian; Condic, Mateja; et al.
Abstract : Introduction/Background: Background: Long-term survivors (>5 years after primary diagnosis) with ovarian cancer (OC) constitute a rare, not well-investigated cohort among OC patients. The recent Expression IV study of the Northeast German Society of Gynecologic Oncology (NOGGO) on patients' preferences and expectations regarding maintenance therapy has shown that patients primarily choose maintenance therapy to improve therapeutic outcome. Only secondarily do they opt for maintenance therapy to improve their quality of life (QoL). Furthermore, approximately 30% of patients prefer an oral administration and over 50% would tolerate a 2-year administration of maintenance therapy if the delay of tumor progression could exceed over six months. Based on these results, this prospective study characterizing the long-term experience of patients with OC undergoing maintenance treatment was planned. The objective of this trial is to prospectively evaluate the long-term survival multifactorial experience in patients undergoing maintenance treatment. In particular, this study aims to identify disease, patient, and treatment factors associated with long-term survival. Methodology: Trial design: Enrollment of 300 patients with platinum-sensitive relapsed OC who are eligible for PARP inhibition in up to 15 sites in Germany and Austria. Treatment decision has to be determined independently by the physician before inclusion of the patients into the study. The niraparib treatment should be planned according to current SmPC. Patients can be included after therapy decision of Niraparib treatment (decision to start Niraparib therapy must have been taken independently) and for up to 3 months after start of Niraparib therapy. During this study data will be collected at baseline and every 3 months for up to 7 years follow-up (long-term survival with every 6 months visits) or patient's death whatever comes first. Since 04/2021 13 patients with maintenance therapy were recruited within the study 'CAROLIN'. Results: / Conclusion: /